Leading to Diversity Management: Case of Community School Head-Teacher's Style in Nepal - Baraily, Khagendra; Rai, Krishna Bahadur (International Research Journal of MMC, 2022)
This study aimed to explore the leadership style of head teacher for the effective diversity management and investigate underlying assumption for respecting difference when act in diversity management the theoretical foundation for this underlying study was constructivist/interpretive the research method adopted for this study was qualitative along with hermeneutics phenomenology. Purposively, four head teachers from rural community schools of Dhankuta District were selected as participant. The participant head teacher were leading schools containing more than four diversities such as age, caste, gender, ethnicity. Profound interview was taken via interview guidelines from the participants based upon the experience in leadership style. Data analysis revealed with the themes of collaboration from the in depth interview and observing an activity of head teacher and services. From the interview protocol the responses had been transcribed and themes were organized to obtain main theme. The major results had been deduced from the main theme. Respect to culture, treating with caste and gender, minorities' advocacy and disability management were the prominent leadership strategies for the succession of school leadership. These strategies are more supportive to diversity management and valuable to conceive as appropriate styles for head teacher to his successful tenure.